Controlling DNA Bundle Size and Spatial Arrangement in Self-assembled Arrays on Superhydrophobic Surface - Ciasca, Gabriele; Papi, Massimiliano; Palmieri, Valentina; Chiarpotto, Michela; Claudio, Simone Di; Ninno, Adele De; Giovine, Ennio; Campi, Gaetano; Gerardino, Annamaria; Businaro, Luca; Spirito, Marco De (Nano-Micro Letters, 2014)
The use of superhydrophobic surfaces (SHSs) is now emerging as an attractive platform for the realization of one-dimensional (1D) nanostructures with potential applications in many nanotechnological and biotechnological fields. To this purpose, a strict control of the nanostructures size and their spatial arrangement is highly required. However, these parameters may be strongly dependent on the complex evaporation dynamics of the sessile droplet on the SHS. In this work, we investigated the effect of the evaporation dynamics on the size and the spatial arrangement of self-assembled 1D DNA bundles. Our results reveal that different arrangements and bundle size distributions may occur depending on droplet evaporation stage. These results contribute to elucidate the formation mechanism of 1D nanostructures on SHSs.